2018
DOI: 10.1017/qua.2018.38
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the erosional impact of a continental-scale drainage capture in the Duero Basin, northwest Iberia

Abstract: Formerly closed drainage basins provide exceptional settings for quantifying fluvial incision and landscape dissection at different time scales. Endorheic basins trap all the sediment eroded within the watershed, which allows estimates of post–basin opening erosion patterns. The Duero Basin was a former closed basin and is presently drained by the Duero River into the Atlantic Ocean. During the Cenozoic, the basin experienced a long endorheic period, marked by the formation of continental carbonates and evapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 63 publications
4
22
0
1
Order By: Relevance
“…Thus, the Early Pleistocene is an important interval for surface development and a key marker for subsequent fluvial landscape incision, both within the Betic Cordillera (this study) and within Iberia [81]. Climate and base level (tectonic and capture) variability are widely cited controlling mechanisms for Early Pleistocene Iberian landscape development [48,[80][81][82]. Surface formation within the Sorbas Basin clearly demonstrates interplay of these factors, but the surface itself probably reflects a sustained period of climate stability and base level position to allow the surface to form autogenically at a basin scale.…”
Section: Timing Of Surface Formationmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, the Early Pleistocene is an important interval for surface development and a key marker for subsequent fluvial landscape incision, both within the Betic Cordillera (this study) and within Iberia [81]. Climate and base level (tectonic and capture) variability are widely cited controlling mechanisms for Early Pleistocene Iberian landscape development [48,[80][81][82]. Surface formation within the Sorbas Basin clearly demonstrates interplay of these factors, but the surface itself probably reflects a sustained period of climate stability and base level position to allow the surface to form autogenically at a basin scale.…”
Section: Timing Of Surface Formationmentioning
confidence: 88%
“…Digital surface reconstruction is a common geomorphological method for analysis of erosional landscapes at a range of spatial and temporal scales [45][46][47][48]. In this study we used the variable Inverse Distance Weighting (IDW var) approach [49] due to similarities of basin scale, landscape morphology and higher quality of method statistical performance.…”
Section: Surface Reconstruction and Erosion Quantificationmentioning
confidence: 99%
“…Although the impact of this significant event has left a perceptible mark on the landscape, such as the partial exhumation of the endorheic filling (Fisher et al, 2007) and the creation of nearly parallel terrace staircases across the basin (Julián, 1996 and references therein), there are no catchment-scale studies to evaluate whether the presumed knickpoints/knickzones that this event generated in the fluvial network are preserved. Deciphering how much the fluvial dissection progressed, how far the regional waves of incision propagated upstream, and how close from a steady state the long profiles are under the new postcapture base level will provide clues on how the landscape evolved in the basin and how ancient the capture was, especially when comparing it with neighbouring basins (e.g., Duero basin; Antón et al, 2012Antón et al, , 2018. In this regard, geomorphic and geologic studies carried out at different locations in the Ebro catchment suggest the existence of prominent knickpoints in the profiles of some of the most important tributaries of the Ebro River; these might reflect that the sectors upstream of these knickpoints graded to a base level that was different from the present one (Stange et al, 2013;Scotti et al, 2014;Lewis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the estimated volume of sediment eroded from the basin is one order of magnitude below that calculated for the Ebro basin (ca. 2800 km 3 vs 25 000–45 000 km 3 ), pointing to a more recent basin opening and/or a slower rate of river incision (Antón et al, ). In the absence of a clear source of tectonic uplift to explain the downstream‐diverging pattern locally observed in terraces T8′–T9, we favour the hypothesis of base‐level fall proposed by previous authors (Pazzaglia et al, ; Colombo, ) to explain the gradients observed in these terraces.…”
Section: Discussionmentioning
confidence: 99%
“…Iberia is well known for its well‐developed endorheic–exorheic transitions in several large basins, among which the Duero and Ebro are the most extensive and show remarkable differences in long‐profile adjustment in response to base‐level lowering (Struth et al, ). The Duero basin is by far the Iberian basin that best preserves the pre‐opening landscape topography compared to other Iberian basins (Antón et al, ). Thus, it has great potential for investigating fluvial terrace architecture in response to endorheic–exorheic transitions (drainage opening), a phenomenon that involves an abrupt lowering of local base level (García‐Castellanos, ; Carroll et al, ; Antón et al, ;) and switches the basin general dynamics from aggradation to incision.…”
Section: Introductionmentioning
confidence: 99%